Foreign Business Activities, Foreignness of the VC Syndicate, and IPO Value. (September 2019) - Chahine, Salim; Saade, Samer; Goergen, Marc
This article examines the role played by foreign venture capital (VC) firms in U.S. initial public offerings (IPOs). We find that U.S. VC–backed IPOs benefit from the foreignness of the VC syndicate. Specifically, jointly with domestic VC firms, foreign VC firms certify the quality of their portfolio companies at the time of the IPO, which increases their IPO premium. Foreign VC firms also play an advisory role, enhancing the foreign business activities of their U.S. investees, thereby increasing the IPO premium. Finally, value added by foreign VC firms is greater through their monitoring role if they originate from countries where the investee has foreign business activities.